1989
DOI: 10.1002/pros.2990140410
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen therapy and liver function—metabolic effects of oral and parenteral administration

Abstract: Oral estrogen therapy for prostatic cancer is clinically effective but also accompanied by severe cardiovascular side effects. Hypertension, venous thromboembolism, and other cardiovascular disorders are associated with alterations in liver metabolism. The impact of exogenous estrogens on the liver is dependent on the route of administration and the type and dose of estrogen. Oral administration of synthetic estrogens has profound effects on liver-derived plasma proteins, coagulation factors, lipoproteins, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…This effect was shown to be associated with elevations in blood pressure and adverse alterations in hepatic metabolism of clotting factors, lipids and other proteins (Schoultz et al 1989). As will be discussed in the 'Potential adverse effects of estrogen therapy' section, these problems might be largely avoided with parenteral administration of non-synthetic estrogens.…”
Section: Past and Present Endocrine Treatments For Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was shown to be associated with elevations in blood pressure and adverse alterations in hepatic metabolism of clotting factors, lipids and other proteins (Schoultz et al 1989). As will be discussed in the 'Potential adverse effects of estrogen therapy' section, these problems might be largely avoided with parenteral administration of non-synthetic estrogens.…”
Section: Past and Present Endocrine Treatments For Prostate Cancermentioning
confidence: 99%
“…Orally administered estrogens induce liver synthesis of coagulation factors, renin substrate, and many carrier proteins including SHBG (Geola et al 1980, Schoultz et al 1989. There are also alterations in lipoprotein metabolism with increases in triglycerides and HDL cholesterol with reduced hepatic cholesterol uptake from HDL (Schoultz et al 1989).…”
Section: Venous Thromboembolism and Cardiovascular Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Veterans' Administration Cooperative Urological Research Group studies on prostate cancer revealed unexpected outcomes; oral oestrogen resulted in improved prostatecancer-specific survival, but overall survival worsened substantially, exposing patients to particularly serious cardiovascular and thromboembolic toxicities arising from oral use 4 . Thus, oral oestrogen, which neces sarily passes through the entero hepatic circulation and bathes the liver in high levels of oestrogen resulting in induction of procoagulant molecules 5 , was soon abandoned 4 .…”
mentioning
confidence: 99%
“…A high concentration of oestrogen in portal blood following oral intake exerts a ‘first pass’ effect on liver-derived plasma proteins, lipoproteins, and triglycerides, and causes an altered production of coagulation factors (increased factor VII and X and decreased antithrombin III) [27]. …”
Section: Oestrogensmentioning
confidence: 99%